PENINGKATAN MOTIVASI BELAJAR DAN KETERAMPILAN DASAR IMPLEMENTASI MPKP MELALUI MEDIA VIDEO DI STIKES BHAKTI AL QODIRI JEMBER - tyas, Eka suryaning (Program Studi Keperawatan dan Kesehatan, Sekolah Tinggi Ilmu Kesehatan (STIKES) Bhakti Al-Qodiri, 2019)
In general, students do not understand broadly the description of the MPKP nursing, pre and post conference rounds. Based on the background of the problem, it encourages the writer to conductfurther research on video media, an increase in motivation to learn and the implementation of MPKPin Nursing undergraduate students, STIKes Al Qodiri Jember. The purpose of this study was todetermine the increase in learning motivation and basic skills of MPKP in the Nursing undergraduatestudents of Stikes Bhakti Al Qodiri Jember. This research design uses quasy experiment. The samplingtechnique uses cluster random sampling, with 15 students as respondents. Analysis of the data used issimple linear regression. the results of statistical tests using simple linear regression on learningmotivation showed that a regression coefficient of 0.451 was obtained with a p value of 0.030. Thismeans that p <α, Ho is rejected and MPKP implementation shows that a regression coefficient of0.277 is obtained with a p value of 0.035. This means that p <α, Ho is rejected.